A Case Study on Key Success Factors of Garuda Indonesia Airlines - Ganatra, Varsha; Sinha, Rupesh; Chawla, Pooja; Yi, Tan Chi; Kee, Daisy Mui Hung; Fei, Neng Mei; Leng, Law Sin; Hui, Foung Hann; Sentosa, Reinaldo Gerald; Sin, Liem Gai; Gupta, Apurv; Pandey, Rudresh (AIBPM Publisher, 2021)
The airline industry plays a vital role in stimulating social, and economic development. Thus, Garuda Indonesia implements various strategies and promotions to face the fast-changing pricing condition and the fierce competitive condition in the local and international markets. This study aims to systematically describe the characteristics of the factors improving Garuda Indonesia Airline’s profitability for its further opportunity exploration and to establish some limitations it is currently facing. To understand how they fully work and to provide more suggestions for the improvements of its overall operational activities, some data will be collected and analyzed.